Speaking through the body: Do people associate the body movements of politicians with their speech?. (27th December 2017) - Koppensteiner, Markus; Siegle, Greg
Abstract : When people speak, they gesture. However, is the audience watching a speaker who is sensitive to this link? We translated the body movements of politicians into stick-figure animations and separated the visual from the audio channel. We then asked participants to match a selection of five audio tracks (including the correct one) with the stick-figure animations. The participants made correct decisions in 65% of all cases (chance level of 20%). Matching voices with animations was less difficult when politicians showed expansive movements and spoke with a loud voice. Thus, people are sensitive to the link between motion cues and vocal cues, and this link appears to become even more apparent when a speaker shows expressive behaviors. Future work will have to refine and validate the methods applied and investigate how mismatches between communication channels affect the impressions that people form of politicians.